Cesare Cases e l’editoria. Un percorso tra pareri e polemiche - Solari, Marco Federici (L’ospite ingrato, 2024)
For almost half a century, Cesare Cases acted as consultant on German literature for the publishing house Einaudi: in hundreds of book reports, he scrutinised the work of the greatest German intellectuals of the 20th century, from Lukács to Adorno, from Brecht to Enzensberger. But his relationship with publishing did not end there. Cases not only worked as a translator, editor, and reviewer of books, actively participating in their promotion and discussion, but, above all, he was an “editorial thinker”, reflecting and intervening on issues such as the relationship between culture and the market, the cultural policies of publishing houses, and, in general, that “exercise in secularisation” that is editorial work. The article also dwells on some recent publications of L’Orma editore, which has republished Cases’ translation and introduction to Bertolt Brecht’s Me-ti.